Government of Nagaland Draft Annual Plan 2009-2010 (Sectoral Plans) Volume 1 - Planning Commission (Planning Commission, 2009)
This is one of the most important schemes of the department. The scheme aims to promote production programme for the food crops other than high yielding varieties that is indented from the firms outside the state such as NSC, SFCI etc which are highly responsive to the chemicals and fertilizers. Apart from the high yielding varieties and other imported notified crop varieties, we have many important food crops indigenous to our state for which the farmer has to be encouraged to produce those organically grown food crops in surplus quantity. Good seeds being the basic necessity for higher food grain production, this scheme aim to introduce the improved seeds/ truthfully labeled seeds having high yielding characteristics and good quality grains to our farmers in the state for higher crop production to meet the increasing demands and to achieve self sufficiency in foodgrains.
Sectoral Plans
Government of Nagaland